Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Let $A$ be an infinite cyclic group and $B$ be a cyclic group of order $n$. Suppose $$0 \to A \to G \to B \to 0$$ is a short exact sequence of abelian groups. What could $G$ be?

It is clear enough that $G = \mathbb{Z} \oplus C_m$ works, for all $m$ such that $m$ divides $n$ and $\textrm{gcd}(m, n/m) = 1$, by the Chinese remainder theorem. $A$ and $B$ are finitely generated, so $G$ is as well; thus the structure theorem for finitely-generated abelian groups tells us that this is exhaustive. However, is there a more direct approach (in the sense of not using a sledgehammer) to this easy-looking exercise? (It is exercise 6.2 in Massey's A basic course in algebraic topology.)

For example, by tensoring with $\mathbb{Q}$, we obtain a right-exact sequence $$\mathbb{Q} \to G \otimes \mathbb{Q} \to 0 \to 0$$ which tells us that the free part of $G$ has rank at most $1$, and considering $\textrm{Hom}(-, \mathbb{Z})$, we get a right-exact sequence $$0 \to \textrm{Hom}(G, \mathbb{Z}) \to \mathbb{Z} \to 0$$ which indicates the free part of $G$ has rank exactly $1$. What can we say about the torsion part?

share|improve this question
    
Actually you do not need the full structure theorem for finitely generated abelian groups, but just the fact that such a group is the direct sum of torsion and torsion-free part. Moreover tensoring with $\mathbb{Q}$ is exact, so that you directly get $\mathbb{Q}\cong G\otimes\mathbb{Q}$. –  Hagen Aug 30 '11 at 9:15
add comment

1 Answer

Consider the short exact sequence

$1 \rightarrow A \xrightarrow{ \phi } G \xrightarrow{ \psi } B\rightarrow 1$

where $\phi(A)=\langle x|- \rangle$ be infinite cyclic group, and $B=\langle \bar{y}| \bar{y}^n\rangle$ be finite cyclic group of order $n$.

($G$ may be abelian or may not be)

Since $G \xrightarrow{ \psi } B$ is surjective, $\exists$ $y\in G$ such that $\psi(y)=\bar{y}$. Then $\psi(y^{n})=\bar{y}^n=1$, so $y^n\in ker(\psi)=\phi(A)$.

Without loss of generality, let $y^{n}=x^{i}$ for some non-negative integer $i$ . It is clear that $G$ is generated by $x,y$.

Also as $A\triangleleft G$, we have $y^{-1}xy\in \phi(A)=\langle x |-\rangle$; so let $y^{-1}xy=x^{j}$ for $j\neq 0$.

Then $y^{-2}xy^{2}=x^{j^2}$, and continuing this $y^{-n}xy^{n}=x^{j^n}$, i.e $x=x^{j^n}$, since $y^n(=x^i)$ commutes with $x$.

So $j^n=1$ in $\mathbb{Z}$. Since $n>0$.

Case1: If $n$ is odd, then $j=1$ is its only solution.

Therefore $y^{-1}xy=x$, which means $G$ is an abelian group; it is quotient of $\mathbb{Z} \oplus \mathbb{Z}$:

$G=\langle x,y | y^{-1}xy=x, y^n=x^i \rangle$

(I didn't find more simplification of this! You may be interested in structure of these groups!)

Case 2: If $n$ is even, then $j=\pm 1$. Case $j=1$ has considered above.

So let $j=-1$. As $y^{-1}xy=x^{-1}$, we have $y^{-1}x^{i}y=x^{-i}$ i.e. $x^{i}=x^{-i}$, since $x^{i}(=y^n)$ commutes with $y$. So $i=0$ i.e. $y^n(=x^i)=1$.

In this case $G$ is semidirect product of $\langle x|- \rangle \cong \mathbb{Z}$, and $\langle y|y^n\rangle \cong \mathbb{Z}/n$.

For this, we have to consider homomorphism from $\mathbb{Z}/n$ into $Aut(\mathbb{Z})\cong \mathbb{Z}_2$. Since $n$ is even, there are only two possibilities of homomorphisms -trivial and $y\mapsto \{x\mapsto x^{-1} \}$.

Therefore $G$ is one of the following:

$G=\langle x,y| y^n, y^{-1}xy=x\rangle \cong \mathbb{Z} \oplus \mathbb{Z}/n$

$G=\langle x,y| y^n, y^{-1}xy=x^{-1}\rangle \cong \mathbb{Z} \rtimes \mathbb{Z}/n$

share|improve this answer
    
In case 2, your claim $x^i = x^{-i}$ is incorrect. Let us take $n = 6$, $G = \mathbb{Z} \oplus C_3$, $x = (2, 0)$, $y = (1, 1)$. Then $y^6 = (6, 0) \ne (-6, 0)$. Nonetheless, $\langle x, y \rangle / \langle x \rangle \cong C_6$. –  Zhen Lin Aug 30 '11 at 10:49
    
$x$ is a generator of infinite cyclic group and $y^n=x^i$ for some $i\in \mathbb{Z}^{+}\cup \{0\}$ (first relation stated after short exact sequence). Also in case 2, $y^{-1}xy=x^{j}=x^{-1}$, so taking $i^{th}$ power both side, we ger $y^{-1}x^{i}y=x^{-i}$ i.e. $y^{-1}y^{n}y=x^{-i}$ i.e. $y^{n}=x^{-i}$ i.e. $x^{i}=x^{-i}$ for $i\in \mathbb{Z}^{+}\cup \{0\}$ which means $i=0$. –  user8186 Aug 30 '11 at 10:58
    
In your example $xy=yx$, whereas in Case 2 considered above, we have relation $y^{-1}xy=x^{-1}$ . From this, and $y^{n}=x^{i}$ with $n>0, i\geq 0$, we have deduced that $x^{i}=x^{-i}$. –  user8186 Aug 30 '11 at 11:05
    
Ah, that's more convincing. You should add that to the post. –  Zhen Lin Aug 30 '11 at 11:11
    
Say $A=\mathbb{Z}$, $B=\mathbb{Z}/2\mathbb{Z}$, and with $y^{-1}xy=x$ as in your first part of case $2$. You seem to be saying at the end that $G$ must be the direct sum of $\mathbb{Z}$ and $\mathbb{Z}/2\mathbb{Z}$, but you can have $G=\mathbb{Z}$, and $\phi$ be the embedding that maps $A$ to $2\mathbb{Z}$. –  Arturo Magidin Aug 30 '11 at 16:08
add comment

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.